Risk factors and symptoms of childhood asthma in students from two schools in Cali (Colombia) - Betancourt-Peña, Jhonatan; Olaya-Tamayo, Rubén Alexander; Giraldo-Mosquera, María Camila; Arredondo-Florez, Erika Julieth; Carrillo, Hugo Alejandro; Ávila-Valencia, Juan Carlos (Universidad y Salud, 2021)
Introduction: Allergies, family history, respiratory infections, low birth weight, and exposure to tobacco smoke are risk factors for asthma, whose symptoms in children include wheezing, dyspnea, and persistent cough. There is a lack of studies about asthma in Cali (Colombia). Objective: To describe risk factors and symptoms in students diagnosed with asthma in two schools from the city of Cali. Materials and methods: A cross-sectional study was developed, which gathered information from caregivers of children aged between 6 and 14 years old using the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Results: Out of the 324 surveys completed by caregivers, 77 children had asthma. 60% of this population were older than 9 years of age, 56% were girls, and 68% belonged to the lower-middle socioeconomic stratum. History of diseases such as child bronchiolitis and asthma and rhinitis in the parents were revealed. Some risk factors that were identified included inadequate flooring of the house, lack of breastfeeding, and attendance to kinder garden. 40.3% of children had dyspnea, cough and wheezing. Conclusions: Risk factors like gender, inadequate flooring, and symptoms such as dyspnea, cough and wheezing were the most frequent in children with asthma.